Improvement of strength – ductility balance of B2-strengthened lightweight steel. (1st June 2020) - Hwang, J.H.; Trang, T.T.T.; Lee, O.; Park, Gyeongbae; Zargaran, A.; Kim, Nack J.
Abstract: The microstructure evolution and tensile properties of a newly designed Fe-21Mn-10Al-1C-5Ni (wt.%) lightweight steel subjected to two annealing conditions (inducing partial recrystallization and full recrystallization) and subsequent aging treatment have been investigated. In the as-annealed condition, the microstructure of the steel consists of polygonal B2 particles along grain boundaries of recrystallized austenite grains and plate-shape B2 particles within unrecrystallized austenite grains, with no B2 bands. In addition, there is a formation of nano-sized κ-carbide and D03 particles within austenite grains and B2 particles, respectively. Subsequent aging promotes the formation of intragranular κ-carbide and D03 nanoparticles within austenite grains and B2 particles, respectively. As a result, the present steel shows an ultrahigh yield strength of 1.6 GPa after aging, which is mainly due to the presence of fine B2 particles within austenite grains and along grain boundaries as well as the additional strengthening effect of nano-sized κ-carbide and D03 particles present in austenite grains and B2 particles, respectively. The steel possesses good ductility (total elongation of 20%) even at such an ultrahigh strength level in the as-aged condition, surpassing the tensile properties of other B2 and κ-carbide strengthened lightweight steels. Graphical Abstract: Image, graphical abstract